MICRO-MODEL FOR RESERVING IN NON-LIFE INSURANCE WITH THE USE OF GENERALIZED LINEAR REGRESSION MODEL EXTENSIONS - Vrobel, Marcel (2018)
This paper develops a deterministic model for individual claim level reserving. The proposed model is based on collected literature and its structure is decomposed and presented as a list of variables. These variables are firstly defined and then predicted with the usage of generalized linear models (GLM) and its extensions in form of Hurdle and Zero-inflated models. These variables are then combined and as a result, a deterministic model for individual claim level reserving model is obtained. For the practical implementation and evaluation, a dataset of MTPL claims, originating from non-insured cars, is used and presented. Based on these claims the estimated reserve is obtained. The model is then compared with a traditional Chain-Ladder model reserve estimate. In the end the proposed model proved to have very accurate predictions but is biased in comparison with the real claim development. The last section suggests how the model can be improved and further developed.